The Development of SOLO Taxonomy Based Assessment Tool on Text of Observation Reports of X Grade Students of Senior High School 1 NA. IX-X - Nining Mindayani; Wisman Hadi; Biner Ambarita (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study is aimed to describe the process of developing SOLO Taxonomy-based assessment tools on the text of observation reports for X grade students of Senior High School 1 NA. IX-X; describe how the appropriateness of the assessment tool, and describe the effectiveness of the assessment tool. This study uses Borg & Gall development model. The analysis is done by determining the characteristics of the will of students and teachers by determining the percentage of answers to each question / statement. The data obtained in this study were quantitative descriptive data. The results showed that: (1) the development of Solo Taxonomy-based assessment tools on the text of observation report was carried out in several stages, there were: research and information collecting; planning; develop preliminary form of product; preliminary field testing; main product revision; and main field testing.  This stages has been restricted to the entire stage of the Borg & Gall development model. Restrictions on the stages of development are tailored to the needs of researchers. All stages are carried out until the product is said to be of good quality based on validity and is suitable for use in learning; (2) the average percentage of all sub-components from the results of the validation of material experts was 81%. The average percentage of all indicators of results to content eligibility was 85.49%; Presentation Feasibility has an average of 88.4%; language worthiness has an average of 90.3%; all three components were in the "excellent" category. The average percentage of all sub-components from the results of the evaluation expert for the multiple choice instrument was 94.38% with "excellent" criteria and the description form had a total percentage of 91.65% with "excellent" criteria. The results of the teacher's response to the assessment tools has an average total percentage of 90.38% with the criteria of "excellent". The results of student’s response to the application of assessment tools has a total percentage of 91.31% with the criteria of "excellent"; and (3) The effectiveness of the Solo taxonomy-based assessment tool on the text of the observation report obtained an average of 82.57. The lowest student score was 75 and the highest was 95. This shows that student learning outcomes were better when compared to without teachers using assessment tools.